2023
DOI: 10.1002/adfm.202214985
|View full text |Cite
|
Sign up to set email alerts
|

Small Changes, Big Impact: Tungsten Bronzes with Extremely Large Second Harmonic Generation Achieved by the Transition Metal Doping on the B‐Site

Abstract: Two novel transition metal-doped tungsten bronze oxides, Pb 2.15 Li 0.85 Nb 4.85 Ti 0.15 O 15 (PLNT) and Pb 2.15 Li 0.55 Nb 4.85 W 0.15 O 15 (PLNW), are synthesized by high-temperature solid-state reactions. The Rietveld method using the high-resolution synchrotron radiation indicates that PLNT and PLNW crystallize in the orthorhombic polar noncentrosymmetric space group, Pmn2 1 (no. 31). As a class of tungsten bronze oxide, PLNT and PLNW retain a unique rigid framework composed of d 0 transition metal cation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…To uncover their electronic structures and optical properties, DFT calculations were carried out. 73,74 As shown in Fig. 4c and d, the band structures indicate that the two compounds are direct band gap semiconductors with calculated GGA band gaps of 2.42 eV for RbB 3 P 2 S 10 and 2.38 eV for CsB 3 P 2 S 10 .…”
mentioning
confidence: 76%
“…To uncover their electronic structures and optical properties, DFT calculations were carried out. 73,74 As shown in Fig. 4c and d, the band structures indicate that the two compounds are direct band gap semiconductors with calculated GGA band gaps of 2.42 eV for RbB 3 P 2 S 10 and 2.38 eV for CsB 3 P 2 S 10 .…”
mentioning
confidence: 76%
“…As an important ferroelectric family next to perovskites, tetragonal tungsten bronzes (TTBs) have been attracting rising attention. Recently, a series of work has emerged on various applications of tungsten bronze ferroelectrics with remarkable performance, including enhancing energy storage properties, , giant piezoresponse, large second-harmonic generation responses, and even enhanced cycling stability, as anodes for ion batteries. , On the other hand, the unique ferroelectric behavior and polarization mechanism of tungsten bronze oxides have received sustained scientific attention, and a number of outstanding research works have been reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…Such a significant NLO technology has been deployed skillfully in numerous cutting-edge fields. [1][2][3][4][5][6][7][8] For an optical application in the mid-far infrared (IR) transmission region, all the dominated NLO crystals, including AgGaS 2 (AGS), AgGaSe 2 (AGSe), and ZnGeP 2 , can have desirable second harmonic generation (SHG) responses. 9 Regrettably, the stubborn drawbacks of low laser-induced damage threshold (LIDT), narrow range of phase-matchable wavelength, and detrimental multiple-phonon absorption occur in the above-mentioned crystals, respectively, thereby hindering their high-power laser applications.…”
Section: Introductionmentioning
confidence: 99%